2020
DOI: 10.21203/rs.3.rs-26240/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Successful COVID-19 rescue therapy by extra-corporeal membrane oxygenation (ECMO) for respiratory failure: a case report.

Abstract: Background: The value of extracorporeal membrane oxygenation (ECMO) for patients suffering from novel coronavirus disease 2019 (COVID-19) as a rescue therapy for respiratory failure remains controversial and associated with high mortality rates of 50% to 82% in early reports from Wuhan, China. We hypothesized that patient outcomes would be improved at our tertiary cardiothoracic surgery referral center with a protocolized team-approach for ECMO treatment of patients with severe COVID-19 disease. Case Presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In our study, six case reports and two case series reported positive endpoints (weaned off ECMO/discharged from hospital) for patients on ECMO 7‐9,11,17,19,23,29 . These outcomes supporting ECMO for COVID‐19 are likely to have occurred for the following reasons.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In our study, six case reports and two case series reported positive endpoints (weaned off ECMO/discharged from hospital) for patients on ECMO 7‐9,11,17,19,23,29 . These outcomes supporting ECMO for COVID‐19 are likely to have occurred for the following reasons.…”
Section: Discussionmentioning
confidence: 71%
“…Third, in cases where the association between COVID‐19, cytokine storm and mortality has been established, 34 the role of ECMO in reducing inflammatory substances has also been attributed to patient survival 23 . ECMO as a therapeutic adjunct has shown promising results in reducing inflammation when utilized in conjunction with primary treatment 9,11,20 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, RDV was shown to have strong inhibitory activities against SARS-CoV-2 in in vitro and animal studies, such as studies of monkeys and mice [6]. Several clinical trials and case reports on patients also support that RDV is a promising candidate for the treatment of COVID-19 [9,10]. However, there are only a few preliminary studies on the in vivo processes of RDV.…”
Section: Introductionmentioning
confidence: 99%
“…Although approximately 70–80% of patients with COVID-19 have mild to moderate symptoms and recover, 5–20% of patients develop severe respiratory failure and may require admission to an intensive care unit (ICU) [ 3 , 4 , 5 ]. Symptomatic treatment for severe respiratory failure has involved the use of mechanical ventilation and extracorporeal membrane oxygenation (ECMO) [ 5 , 6 , 7 , 8 , 9 ], although there are candidate drugs available to treat severe patients with COVID-19 as of September 2020 [ 10 , 11 ]; remdesivir [ 12 , 13 ] and dexamethasone [ 14 ]. One study that analyzed clinical cases of COVID-19 reported a better prognosis in patients with a mild infection, whereas the prognosis for patients with severe and critical infections is poor.…”
Section: Introductionmentioning
confidence: 99%